Study On Effect Of Brand Credibility On Word Of Mouth With Reference To Internet Service Provider In Malaysia - Seyed Ghorban, Zahra (2011)
This study tried to investigate the effect of brand credibility on word of mouth among customers through their satisfaction and loyalty. Word of mouth has been shown to be an important factor in customers\' decision behavior. They reflect by word of mouth positively and negatively. Brand credibility refers to the psychological elements that can influence the customers buying behaviors and it can create positive or negative effect. On the other hand the behaviors that form the word of mouth consider as the informal sharing of any purchase or consumption related information among customers. Word of mouth is considered to consist of two general types: negative and positive word of mouth. Despite there have been studied targeting issues of brand, satisfaction and loyalty, this study included word of mouth to these issues to fill the existing gap in the internet service providers in Malaysia.